2013
DOI: 10.1253/circj.cj-12-0148
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Cystatin C in the Postoperative Management of Pediatric Patients With Congenital Heart Disease

Abstract: Cys-C may be a useful marker of renal function in terms of hemodynamic status in the postoperative management of CHD, although its superiority over Cr could not be confirmed. Future studies should clarify the role of Cys-C in clinical decision-making and evaluate the relationship of Cys-C with factors that may affect its levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Moreover, a previous study reported that CysC itself is useful for evaluating renal function after CHD surgery. 10) The hemodynamics of patients after biventricular repair are not extremely different from those of healthy people; hence, only few studies on how cardiac function abnormalities in the remote postoperative period affect the renal function and on early evaluation of renal function have been conducted. Elevated UACR (i.e., 30 to 300 mg/gCr) is originally an early predictor of progressive renal function loss in types 1 and 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a previous study reported that CysC itself is useful for evaluating renal function after CHD surgery. 10) The hemodynamics of patients after biventricular repair are not extremely different from those of healthy people; hence, only few studies on how cardiac function abnormalities in the remote postoperative period affect the renal function and on early evaluation of renal function have been conducted. Elevated UACR (i.e., 30 to 300 mg/gCr) is originally an early predictor of progressive renal function loss in types 1 and 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%